Greek and Roman art - Woodford, Susan (Art essentials., 2020)
"For more than 2,000 years the art of Greece and Rome has lain at the heart of western civilization. This book recaptures the excitement of the artists who first created it. It traces the daring innovations of those who, defying traditional wisdom, explored new ideas; it describes the valiant struggles of sculptors and painters to portray - for the first time - both the complexities of the human form and the richness of human emotions. So much has been destroyed by the ravages of time that Greek and Roman art seems to consist only of impressive ruins and broken fragments. Yet the creative achievements of the Greeks and their legacy, as adapted by the Romans, have never lost their power."--Page [2] of cover.